Flower thrips, Frankliniella tritici (Fitch) (Insecta: Thysanoptera: Thripidae) - Danielle Sprague; Joseph E. Funderburk; Andrea Lucky (EDIS)
The flower thrips, Frankliniella tritici (Fitch) (Figure 1), is one of the most abundant species of flower thrips (Thysanoptera: Thripidae) in the eastern United States (Reitz 2008). The official common name established by the Entomological Society of America for this species is flower thrips, although the name flower thrips is often applied generically to the numerous species in the genus Frankliniella that inhabit flowers. For this reason, it is frequently referred to as the eastern flower thrips, presumably for its distribution in the eastern United States.